Progression Measurement of Visual Field Loss in Medically Controlled Primary Open-Angle Glaucoma (POAG) - Maham Zehra; Mohd Shakaib Anwar; Erum Yousafzai; Waseem Akhter; Qura -Tul- Ain; Maeirah Shafique (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine mean visual field parameters loss (Mean deviation and Pattern standard deviation) and frequency of glaucoma hemifield test to evaluate optic nerve damage progression in medically well-controlled primary open-angle glaucoma POAG through standard automated perimetry.